Multidisciplinarni pristup kod seksualne disfunkcije žena u sportu - Schuster, S.; Sklempe Kokic, I.; Elvedi Gasparovic, V.; Ajdukovic, D. (Croatian Sports Medicine Journal, 2017)
Sexual dysfunction is registered as an ever increasing problem that occurs equally in men and women. In women who are actively involved in sports sexual dysfunction has so far not been sufficiently studied. In most cases, the problem of sexual dysfunction is more likely as age increases. Lack of interest in sexual relations and the inability to achieve orgasm in women, as well as premature ejaculation in men, are the most common sexual problems. Etiology of sexual dysfunction is complex and related to changes in the vascular, neurological, endocrine and muscular system. Types of sexual dysfunction in women include reduced sex drive, orgasmic disorders and painful intercourse. Female athletes can have all types of sexual dysfunctions, and alongside complex medical treatment, kinesiology-anthropological analyses and physiotherapy process should also be implemented, which would define the need, type and extent of therapeutic exercises as part of a multidisciplinary treatment.